ANALISIS SIFAT KIMIA TANAH PADA LAHAN HORTIKULTURA DI DESA LADOGAHAR KABUPATEN SIKKA - Agustinus Sterip Erikson; Yovita Yasintha Bolly; Almaria Heliana (Agriculture Faculty of Flores University, 2021)
Soil is one of the main components that affect agricultural productivity. Soil quality certainly needs to be considered as an effort to increase plant growth and production. One of the most influential components of soil quality is the chemical nature of the soil. Research on Analysis of Soil Chemical Content in Horticultural Farmers' Land in Ladogahar Village, Nita District, Sikka Regency has been carried out from October to December 2021. The purpose of this study was to determine the chemical content of the soil in Horticultural Farmers' Land in Ladogahar Village, Nita District, Sikka Regency. This research uses observation methods, literature studies, and laboratory tests. Composite soil sampling using the zigzag method. The results showed that the land had a low C-organic content (1.00-2.00%), a slightly acidic pH (5.6-65), a low phosphorus content (21-40), and a Potassium content in the soil. moderate range (21-40).